2019
DOI: 10.1002/spe.2774
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for long‐term software security: Creating a lightweight program of assurance techniques for developers

Abstract: Though some software development teams are highly effective at delivering security, others either do not care or do not have access to security experts to teach them how. Unfortunately, these latter teams are still responsible for the security of the systems they build: systems that are ever more important to ever more people. We propose that a series of lightweight interventions, six hours of facilitated workshops delivered over three months, can improve a team's motivation to consider security and awareness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Its advantage over SATs is primarily that it can operate on code where the full source is not available, such as with apps with third-party libraries that download and run code during execution. Both static and dynamic analysis provide useful insights for testing, but neither are comprehensive [102]. While we focus on SATs in this paper, our findings would likely apply to dynamic analysis notification content as well.…”
Section: Static Analysis Tools (Sats)mentioning
confidence: 97%
See 1 more Smart Citation
“…Its advantage over SATs is primarily that it can operate on code where the full source is not available, such as with apps with third-party libraries that download and run code during execution. Both static and dynamic analysis provide useful insights for testing, but neither are comprehensive [102]. While we focus on SATs in this paper, our findings would likely apply to dynamic analysis notification content as well.…”
Section: Static Analysis Tools (Sats)mentioning
confidence: 97%
“…SATs can work without needing to run the code itself so they can be integrated into IDEs or even work off of websites which makes it easier for developers to find and fix defects earlier in the development process rather than waiting till the test and production stages. SATs are recommended as the first line of defence against vulnerabilities [102], and developers have previously acknowledged their usefulness in finding security vulnerabilities [97]. Various academic researchers recommend developers use SATs [45,58,86,101,102], and they are also used by large technology companies such as Microsoft [22,91], Facebook [31], and Google [5,7,82,83], as well as in open-source projects such as Linux, Firefox, and Qt [14,48,99,105].…”
Section: Introductionmentioning
confidence: 99%
“…• Motivate developers to drive their own security improvements [36]; • Encourage developers to adopt a subset of key assurance techniques, specifically Threat Assessment, Configuration Review, Automated Static Analysis, Source Code Review, and Penetration Testing [36];…”
Section: The Interventionmentioning
confidence: 99%
“…• Incentivization Session, and • Threat Assessment Based on early trials of a workshop-based intervention [36] we concluded two further requirements:…”
Section: The Interventionmentioning
confidence: 99%
See 1 more Smart Citation